2007
DOI: 10.1128/iai.01011-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll-Like Receptor 9 in Legionella pneumophila -Induced Interleukin-12 p40 Production in Bone Marrow-Derived Dendritic Cells and Macrophages from Permissive and Nonpermissive Mice

Abstract: The progression of Legionella pneumophila infection in macrophages is controlled by the Lgn1 gene locus, which expresses the nonpermissive phenotype in cells from BALB/c mice but the permissive phenotype in cells from A/J mice. Activation of dendritic cells and macrophages by L. pneumophila is mediated by the pathogen recognition receptor Toll-like receptor 2 (TLR2); furthermore, Legionella induces innate and adaptive immune cytokines by the MyD88-dependent pathway. TLR9 is coupled to MyD88 and mediates the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
4
29
0
1
Order By: Relevance
“…Previous studies used knockout mice and BMD macrophages from these knockout mice to demonstrate that during intracellular infection, L. pneumophila stimulates TLRs, including both cell surface TLR2 (via the recognition of lipoprotein and LPS) and TLR5 (flagellin) and intracellular TLR9 (CpG oligodeoxynucleotide) (64)(65)(66)(67)(68)(69). In order to test, for the first time, the importance of these pathways in human macrophages, we started out by generating a stable knockdown of MyD88 with a 76% decrease in protein expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used knockout mice and BMD macrophages from these knockout mice to demonstrate that during intracellular infection, L. pneumophila stimulates TLRs, including both cell surface TLR2 (via the recognition of lipoprotein and LPS) and TLR5 (flagellin) and intracellular TLR9 (CpG oligodeoxynucleotide) (64)(65)(66)(67)(68)(69). In order to test, for the first time, the importance of these pathways in human macrophages, we started out by generating a stable knockdown of MyD88 with a 76% decrease in protein expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data address an important question in microbial recognition regarding redundancy among TLRs. L. pneumophila is recognized by several TLRs including TLR2, TLR4, TLR5, and TLR9 (17)(18)(19)(20)(22)(23)(24). Interestingly, Legionella LPS signals predominantly through TLR2, rather than TLR4, suggesting an important role for TLR2 in Legionella recognition (18).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs recognize microbes at the plasma membrane or within organelles, such as phagosomes and endosomes, while NLRs mediate pathogen recognition in the cytosol. We, and others, have used in vitro and in vivo studies to demonstrate that L. pneumophila is recognized by several TLRs including TLR2, TLR4, TLR5, and TLR9 (17)(18)(19)(20)(21)(22)(23)(24). Using human genetic studies, we previously found that a common stop codon polymorphism in TLR5, a receptor for bacterial flagellin, abrogates signaling and is associated with altered susceptibility to Legionnaires' Disease (20).…”
mentioning
confidence: 99%
“…Several studies have reported that TLRs contribute to the host response against L. pneumophila during in vitro and in vivo infection (Girard et al, 2003;Kikuchi et al, 2004;Akamine et al, 2005;Hawn et al, 2006Hawn et al, , 2007Fuse et al, 2007;Newton et al, 2007). However, there have been no studies to elucidate immunostimulatory properties of isolated individual proteins from L. pneumophila in terms of engagement of TLRs and linking to elicit the antigen-specific adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%